The effect of different milk pricing schemes on a selection index for South African Holstein cattle - Tesfa, Kal'ab Negash (University of the Free State, 2002)
English: A total of 150673 first lactation records of South African Holstein lactating cows were used to estimate the genetic parameters of milk (MY), butterfat (BFY), and protein (PRY) yields, and butterfat (BFP) and protein (PRP) percentages. The data comprising 113 056 dams and 1 429 sires, distributed over 1 205 herds, were collected over a period of 21 years, 1980 to 2000. The study was aimed at the following aspects: to determine the non - genetic factors influencing milk traits for use in the model for a subsequent genetic analysis; to estimate the variance-covariance components and heritabilities of all traits. Finally, to calculate the weighting factors for a selection index and predict the expected response to selection when using different milk pricing systems. Five fixed effects were defined, viz: milking frequency, age at calving, herd, month of calving and year of calving. Analysis of variance indicated that all effects were highly significant (p < 0.0001) explaining on average 64.60%, 62.96%, 64.36%, 15.66% and 23.86% of the total variation for MY, BFY, PRY, BFP and PRP, respectively. Considering the R2 and RMSE as an option, month of calving for all traits, milking frequency for BFP and PRP, and age at calving for PRP showed a minor contribution to the variation and were, thus, excluded from the model for the subsequent analysis. Heritability estimates varied from medium for BFY and PRY to high for MY, BFP and PRP. This indicates that faster genetic progress will be possible through selection of MY, BFP and PRP. The highly positive genetic correlation among yield traits indicates selection for milk yield will result in a favourable response with butterfat and protein yield. However, it will lead to an unfavourable response to selection for the percentage traits. This is due to a negative genetic correlation between milk yield with percentage traits. Using the Desire program, weighting factors and expected response per generation for milk, butterfat and protein yield were calculated under three milk buyers (A, B and C) pricing systems. The standard deviations of alternative breeding objectives and selection indices were also calculated. The weighting factors for milk, butterfat and protein yields were 0.16, 2.41 and 3.24 for milk buyer A, 0.04, 3.43 and 5.70 for milk buyer Band 0.03, 3.48 and 4.37 for milk buyer C, respectively. While the expected response for the corresponding traits, when the intensity of selection equals one, were +546kg, + 16.6kg and + 15.6kg for MY, BFY, PRY respectively. in the ease of milk buyer A, +509kg, +17.1kg and +15.7kg for milk buyer B and +504kg, + I7.3kg and + I5.5kg for milk buyer C. The correlations of indices of B and C with respect to index A were 0.97 and 0.84, respectively. This indicates that the loss of efficiency when selection index Band C were used is 3 % and 16 %, respectively. Rankings of Holstein cows under the three milkpricing systems were different and this indicates that depending on the choice of their breeding goals South African Holstein breeders should follow different selection programs.

Afrikaans: 'n Totaal van 150673 eerstelaktasierekords van Suid-Afrikaanse Holsteinkoeie is gebruik om genetiese parameters van melk- (MO), bottervet- (BVO) en proteïnopbrengste (PRO) te beraam, asook bottervet- (BVP) en proteïnpersentasies (pRP). Die data wat 113 056 koeie en 1 429 vaars bevat, versprei oor 1 205 kuddes, is oor 'n periode van 21 jaar, 1980 - 2000, ingesamel. Die studie is op die volgende aspekte gerig: om die nie-genetiese faktore te bepaal wat melk-eienskappe affekteer vir gebruik in die model vir 'n genetiese ontleding; om die variansie-kovariansie komponente en oorerflikhede van alle eienskappe te beraam; en ten laaste, om die wegingsfaktore vir 'n seleksie-indeks te bereken en die verwagte responsie op seleksie wanneer verskillende melkpryssisteme gebruik word. Vyf vaste effekte is gedefinieer, nl. melkfrekwensie, ouderdom met kalwing, kudde, maand van kalwing en jaar van kalwing. Ontleding van variansie het aangetoon dat alle effekte hoogs betekenisvol (p<.0001) was, wat gemiddeld 64.6%, 62.96%, 64.36%, 15.66% en 23.86% van die totale variasie vir MO, BVO, PRO, BVP en PRP onderskeidelik verklaar het. Met R2 en RMSE as 'n opsie het maand van kalwing vir alle eienskappe, melkfrekwensie vir BVP en PRP en ouderdom met kalwing vir PRP 'n baie klein bydrae tot die variasie gemaak en is dit dus uit die model gelaat vir die volgende ontleding. Oorerflikheidsberamings het gewissel van medium vir BVO en PRO tot hoog vir MO, BVP en PRP. Dit is 'n aanduiding dat vinniger genetiese vordering moontlik sal wees deur seleksie van MO, BVP en PRP. Die hoogs positiewe korrelasie toon aan dat seleksie vir melkopbrengs 'n gunstige responsie met bottervet en proteïnopbrengs tot gevolg sal hê. Dit sal egter tot 'n ongunstige responsie lei op seleksie vir die persentasieeienskappe. Dit is te wyte aan 'n negatiewe genetiese korrelasie tussen melkopbrengs met persentasie -eienskappe. Onder die Desire-program is wegingsfaktore en verwagte responsie per generasie vir melk, bottervet en proteïnopbrengs bereken onder drie melkkopers se pryssisteme. Die standaardafwykings van alternatiewwe teeltdoelwitte en seleksie-indekse is ook bereken. Die wegingsfaktore vir melk, bottervet en proteïnopbrengste was 0.16, 2.41 en 3.24 vir melkkoper A, 0.04, 3.43 en 5.70 vir melkkoper B en 0.03, 3.48 4.37 vir melkkoper C onderskeidelik. Die verwagte responsie vir die korresponderende eienskappe met die intensiteit van seleksie gelyk aan een, was +546kg, +16.6kg en +I5.6kg vir MO, BVO en PRO onderskeidelik in die geval van melkkoper A, +509 kg, + 17.1 kg en +15.7 kg Vir melkkoper Ben 504kg, +17.3 kg en 15.5 kg vir melkkoper C. Die korrelasie van indekse van B en C ten opsigte van indeks A was 0.97 en 0.84 onderskeidelik. Dit dui aan dat die verlies van doeltreffendheid met gebruik van seleksieindeks B en C 3% en 16% onderskeidelik was. Rangskikking van Hosteinkoeie onder die drie melkpryssisteme het verskil en dit dui aan dat Suid-Afrikaanse Holsteintelers verskillende seleksieprogramme moet volg na gelang van die keuse van hul teeltdoelwitte.
Keywords: Holstein-Friesian cattle; Selection indexes (Animal breeding); Milk -- Prices; Dissertation (M.Sc.Agric. (Animal, Wildlife and Grassland Sciences.))--University of the Free State, 2002